(untitled) (American Journal of Arts and Human Science, 2023)
Reactions in Nigeria to Adichie’s letter to the US President after the election were mixed, particularly leading to a reactive letter from Oke to the US President and Canadian Prime Minister. The complexity and diversity of Nigerian politics, as well as the challenges of striking a healthy balance between the demands for openness and accountability and the worries about national sovereignty and outside interference, is illuminated by an in-depth analysis of the perspectives and perceptions held by Nigerians with regard to the 2023 presidential elections outcome that prompted the letters. Hence, the study on reconciling the conflicting perceptions of electoral accountability versus national sovereignty in Adichie’s and Oke’s post-election letters to the American governments aims to present a variety of Nigerians’ perspectives in regards to the outcome of the presidential election, to consider the alleged electoral malpractices in the Election and how these prompted the letters to the American governments and to reconcile the conflicting perspectives of openness/accountability (Adichie’s Letter) and national sovereignty/interference (Oke’s Letter). The study is built on the frame of the agenda-setting theory. The paradigmatic analysis method is employed and the study’s discourse is further divided into four paradigms. The study concludes that all matters must be handled on the basis of deliberate patriotism and without any sentiment of ethnic biases as was perceived by Nigerians in order to resolve the tension between Adichie and Oke’s letters, which present opposing views on the importance of openness and accountability and the value of independence and national sovereignty, respectively.